The Enforcement of Federal Laws in States in Ethiopian Ethnic Federalism: The Deadlock between the Federal Government and the Tigray Regional State on the New Law of Boundaries and Identity Issues - Ayana Simachew Bekele (European Scientific Journal, ESJ, 2019)
Intergovernmental relations are the responses that have been developed to facilitate cooperative policy making among divided governments within a federal system. Intergovernmental relations are supposed to play a bridge-building role to bring a degree of coordination and cooperation to divided powers. Enforcing federal laws in the states is one form of the interactions between the federal governments and states in federations. Today enforcement of federal laws and policies in the state in particular and the task of intergovernmental coordination in general are mainly done through the ruling party (EPRDF). Execution of federal laws and policies in the states using a party line has been made smoothly for the last 28 years in Ethiopia. However, following the coming of PrimeMinister Abiy to power, EPRDF lost the support of TPLF, its core allies on its stand in the process of enacting and executing policies and laws. It, in turn, has led to gaps in the regularity and effectiveness in the implementation of federal laws in the states. Excessive reliance on party channel evokes the question of what will happen if more members( alliances) manage to depart from the ideology of the EPRDF and whether under such contexts bring about the collapse of the Ethiopian federalism as well. Such risks call for the need to establish vibrant institution to coordinate the execution of federal laws in the states in Ethiopian federal system.